Strongyloides stercoralis prevalence and diagnostics in Vientiane, Lao People's Democratic Republic - Somaphone Chankongsin; Rahel Wampfler; Marie-Therese Ruf; Peter Odermatt; Hanspeter Marti; Beatrice Nickel; Valy Keoluangkhot; Andreas Neumayr (BMC, 2020)
Abstract Background Despite the high prevalence of strongyloidiasis in the Laotian population, Laotian hospitals still lack diagnostic capacity to appropriately diagnose Strongyloides stercoralis infections. This cross-sectional hospital-based study was conducted to assess the prevalence of Strongyloides stercoralis infection among hospitalized patients treated at Mahosot Hospital, the primary reference hospital of Lao People's Democratic Republic (Lao PDR), and to validate feasible methods for diagnosing S. stercoralis infection at hospital's laboratory. Methods Between September and December 2018, stool samples of 104 inpatients were investigated for S. stercoralis infection by wet smear, Baermann technique, Koga Agar plate culture (KAPC), and real-time detection polymerase chain reaction (RTD-PCR) at the Infectious Diseases Ward of the Mahosot Hospital in Vientiane. The sensitivity, the specificity, the negative predictive value (NPV) of each diagnostic test, as well as their combination(s) was calculated using a composite reference standard (CRS). The correlation of the different test methods was assessed by chi-square or Fisher's exact test. Cohen's kappa coefficient was used to assess the diagnostic agreement of the different test methods. Results The overall prevalence of S. stercoralis infections among the study population was 33.4%. The cumulative infection prevalence statistically significantly increased from the lowest age group of 40 years and below (22.4%), to the medium (40.0%) and to the oldest age group of 61 year and above (72.7%)(P = 0.003). The cumulative infection prevalence of CRS was considerably higher in male (40.4%) compared to female patients (28.1%), but not statistically different (P = 0.184). The diagnostic sensitivity of Baermann technique, KAPC, RTD-PCR, and the combination of Baermann technique and KAPC were 60.0, 60.0, 74.3, and 77.1%, respectively. Only 13 patients (37.1%) of the total 35 S. stercoralis patients diagnosed with any technique had a simultaneously positive diagnostic test with Baermann, KAPC and RTD-PCR. Conclusions We identified Baermann technique and KAPC to be currently the most feasible and implementable standard methods for diagnosing S. stercoralis at a hospital setting such as Mahosot Hospital and provincial and district hospitals in Lao PDR and other low- and middle income countries in Southeast Asia. Trial registration This study was approved by the National Ethics Committee for Health Research in Lao PDR (reference no. 083/NECHR) and by the Ethics Committee Northwest and Central Switzerland (reference no. 2018-00594).